Antithrombotic Drugs in the Primary Medical Management of Intermittent Claudication: A Meta-analysis - Girolami, Bruno; Bernardi, Enrico; Prins, Martin H.; Wouter ten Cate, Jan; Prandoni, Paolo; Hettiarachchi, Rohan; Marras, Elena; Maria Stefani, Piero; Girolami, Antonio; Büller, Harry R. (Thrombosis and Haemostasis, 1999)
Background. There is no consensus on the efficacy of the antithrombotic drugs available for patients with intermittent claudication. Methods. A Medline and manual search was used to identify relevant publications. Uncontrolled or retrospective studies, double reports or trials without clinical outcomes were excluded. Included studies were graded as level 1 (randomised and double- or assessor-blind), level 2 (open randomised), or level 3 (non-randomised comparative). Mortality, cerebro- or cardiovascular events, amputations, arterial occlusions or number of revascularization procedures performed in the lower limbs, pain-free and total walking distance, ankle brachial index and calf blood flow, were the main outcomes considered. When feasible, end of treatment results, either continuous or binary, were combined with appropriate statistical methods. Results. Mortality was significantly decreased by ticlopidine compared to placebo (common odds ratio 0.68, 95% C.I., 0.49 - 0.95); clopidogrel decreased vascular events in comparison to aspirin (odds ratio 0.76, 95% C.I., 0.63 - 0.92) in level 1 studies. Arterial occlusions and the number of revascularization procedures performed were statistically significantly decreased by aspirin and ticlopidine, respectively. A small but statistically significant improvement in pain-free walking distance was determined by picotamide, indobufen, low molecular weight heparins, sulodexide and defibrotide, in small studies. Conclusions. Clopidogrel and ticlopidine do reduce clinically important events in patients with intermittent claudication and could be added to the primary medical treatment of these patients. The use of aspirin in these patients cannot be based on direct evidence, but only on analogy with coronary and cerebral atherosclerosis, where it has documented efficacy. Other antithrombotic drugs were not properly evaluated in patients with intermittent claudication.